2008
DOI: 10.1088/0953-8984/20/49/494223
|View full text |Cite
|
Sign up to set email alerts
|

Influence of particle composition and thermal cycling on bijel formation

Abstract: Abstract. Colloidal particles with appropriate wetting properties can become very strongly trapped at an interface between two immiscible fluids. We have harnessed this phenomenon to create a new class of soft materials with intriguing and potentially useful characteristics. The material is known as a bijel: bicontinuous interfacially-jammed emulsion gel. It is a colloid-stabilized emulsion with fluid-bicontinuous domains. The potential to create these gels was first predicted using computer simulations. Exper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…In a previous study [32] we began investigating the interaction between the modified silica surfaces and the water-lutidine system. We systematically varied the concentration of dye (fluorescein isothiocyanate) used to prepare the particles, finding that with increasing dye loading, the particle surfaces become more hydrophilic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study [32] we began investigating the interaction between the modified silica surfaces and the water-lutidine system. We systematically varied the concentration of dye (fluorescein isothiocyanate) used to prepare the particles, finding that with increasing dye loading, the particle surfaces become more hydrophilic.…”
Section: Discussionmentioning
confidence: 99%
“…Early in the development of WL bijels we observed that if the same sample was subjected to repeated cycles of heating (phase separation) and cooling (re-mixing), the wetting preference of the particles moved gradually towards the L-phase [32].…”
Section: Effect Of Exposing the Particles To Lutidinementioning
confidence: 90%
See 1 more Smart Citation
“…In the water/oil systems, short-ranged attraction stems from the van der Waals force between particles while long-ranged repulsion is due to the weak, negative electrostatic charge of the dissociated silanol groups on the surface of hydrophilic particles (P-SNP). 20,48 When B-SNP were used to stabilize the polar bijels (e.g. bijel of nitromethane and ethylene glycol), the HMDS graft layers on B-SNP hindered the formation of monogel.…”
Section: Formation Of Monogelmentioning
confidence: 99%
“…This is an important consideration, as it has been shown that the presence of APTES on the silica surface is crucial for meeting the neutral-wetting requirement in the W-L system [18,19] -it has been suggested that the surface decorations act to disrupt the wetting layer of lutidine which spontaneously forms around the particles when approaching the phase separation temperature [20,21]. For the NPs, DLS returned a particle radius of 0.08 µm and TEM returned 0.063 µm with a polydispersity of 15% (Fig.…”
Section: B Particle Synthesismentioning
confidence: 99%